Manipulating size, amount and appearance of food inputs to optimize supplementary feeding programs for European vultures. (January 2015) - Moreno-Opo, Rubén; Trujillano, Ana; Arredondo, Ángel; González, Luis Mariano; Margalida, Antoni
Highlights: We performed an experimental videomonitored trial in supplementary feeding sites. The selection of carrion characteristics by feeding European vultures was studied. Less priority species was favored by inputs of great sized unscattered carcasses. Endangered vulture species optimized food intake with dispersed small pieces. Age-classes segregated prey selection being adults more specialized and competitive. Abstract: Supplementary feeding is one of the most common techniques used to alleviate threats to scavengers species related to the quality and availability of food resources. Because supplementary feeding may have undesired effects, the management of supplementary sites should be optimized from an ecological and conservation perspective. We installed high-resolution videocameras at six Spanish feeding stations recording more that 7500 h of observations at 105 feeding events. We analyzed food preferences in the four European vulture species (Eurasian griffon vulture Gyps fulvus, Egyptian vulture Neophron percnopterus, bearded vulture Gypaetus barbatus and cinereous vulture Aegypius monachus ) as they relate to the characteristics of the food remains and carcasses provided at feeding sites. Our results suggest that carrion features (format, scattering, prey species, biomass and items) influence differential selection between species and age-classes. At a species level, large inputs of unscattered carrion increased the abundance of actively feeding griffon vultures. The ratio of the abundance of bearded vultures, Egyptian vultures and cinereous vultures with respect to griffon vultures was favored when less biomass was supplied and when the food provided was not presented as whole carcasses. Thus, using medium-size ungulates (i.e. sheep and goats) presented as small, abundant and scattered pieces favors the consumption of the resource by the most endangered species. Our findings can be used to optimize the supplementary provisioning of vultures in cases where this conservation tool is considered essential for managing targeted species or population groups.